Partisan Bias in Economic News Content: New Evidence. Issue 6 (November 2019) - Merkley, Eric
Claims that the mainstream media are biased in favor of the Democratic Party are commonplace. However, empirical research has yielded mixed results and neglected potential bias in the dynamics of media behavior. This article contributes to this literature by using time series analyses of the dynamics in media tone based on more than 400, 000 stories on inflation and unemployment from top-circulating American print media and the Associated Press newswire. The results suggest there is bias in favor of Democratic presidents. Media tone in unemployment and inflation coverage is more favorable during Democratic presidencies after controlling for economic performance. Tone is also generally more responsive to negative, short-term changes in economic conditions during Republican presidencies. In other words, bias is stronger with worsening economic conditions.